The Effect of Communication and Work Facilities Through Public Service Quality on Public Satisfaction at The Regional Revenue Agency of West Tanjung Jabung District - Fitriani, Dian; Yamali, Fakhrul Rozi; Mufidah, Mufidah (Dinasti International Journal of Management Science, 2026)
This study aims to analyze the influence of communication and work facilities on public satisfaction through the quality of public services at the Regional Revenue Agency of West Tanjung Jabung Regency. Public satisfaction is a crucial indicator in assessing the success of public service delivery, particularly in local government agencies that interact directly with the public. This study employed a quantitative approach with a survey method. The population comprised all 106,877 taxpayers registered with the Regional Revenue Agency of West Tanjung Jabung Regency. The sample size was determined using the Slovin formula with a 10% error tolerance, resulting in a sample size of 100 respondents. Data were collected through a questionnaire structured based on the variable indicators of communication, work facilities, public service quality, and public satisfaction. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that communication and work facilities had a positive and significant effect on public service quality. Furthermore, public service quality had a positive and significant effect on public satisfaction. The test results also demonstrated that public service quality mediated the influence of communication and work facilities on public satisfaction. These findings emphasize the importance of improving effective communication and providing adequate work facilities to enhance the quality of public services and public satisfaction.